Kullanımlar ve Doyumlar Yaklaşımı Bağlamında Televizyon İzleme Alışkanlıkları ve Motivasyonları: Çankırı Karatekin Üniversitesi Örneği. - Kalaycı, Hakkı; Doğan, Şahin (Electronic Turkish Studies)
The aim of this research is to investigate the factors affecting the television viewing habits and motivations of students continuing their education at Çankırı Karatekin University. A face-to-face questionnaire was randomly applied to 703 participants aged 15 and over at Çankırı Karatekin University, and as a result of the analysis, it was seen that the answers were collected in four factors. We named these factors as guidance, information, recreation, entertainment, and friendship. The four factors explain 63.282% of the total variance. As a result of the test, the “Cronbach Alpha” reliability coefficient was found to be 0.87.On average, 2–3 hours of television are watched per day. On weekdays and weekends, people watch television most intensively between 21.00 and 23.00 hours. In program preferences, entertainment programs are preferred in the first degree and news programs in the second degree; in channel selection, quality, entertainment, and compliance with moral values are most important. The field-based analysis of variance (ANOVA) showed that students in the health and science sciences like programs that will help them with their daily lives, while students in the social sciences like programs that will give them information. Students in the social sciences and science also like programs that will help them relax and have fun more than students in the health sciences, and students in the science and health sciences also like programs that will help them make friends and stop being lonely.In the comparison made on the basis of faculties and colleges (ANOVA), it was concluded that the students of the Faculty of Humanities and Social Sciences prefer programs for guidance relatively less than the students of other faculties and colleges; on the contrary, they prefer programs for obtaining information intensively. The students of the Faculty of Science and the Faculty of Economics and Administrative Sciences prefer programs for obtaining knowledge relatively less than the students of the Faculty of Humanities and Social Sciences, but the students of the Vocational School, Faculty of Engineering, and Faculty of Health Sciences prefer them more. It has been observed that the students of the Faculty of Humanities and Social Sciences are significantly ahead of the other groups, except for the students of the Faculty of Science, in their preference for programs for recreation and entertainment; however, the students of the Faculty of Science prefer such programs more than the students of the Vocational School and the Faculty of Engineering. It is concluded that the students of the Faculty of Economics and Administrative Sciences and the students of the Faculty of Engineering prefer programs for recreation and entertainment compared to the students of the Faculty of Health Sciences. It is noteworthy that these types of programs are least preferred by the students of the Faculty of Health Sciences. It was observed that programs such as befriending and eliminating loneliness were least preferred by the students of the Faculty of Humanities and Social Sciences, moderately preferred by the students of the Faculty of Economics and Administrative Sciences, and most preferred by the students of the Faculty of Engineering.